Geographic information systems and environmetal modeling (Prentice Hall, 2002)
This book provides readers with the most comprehensive and authoritative treatment of the topic available. Topics covered include modeling frameworks, paradigms and approaches; model development, calibration and validation; dynamic systems modeling and four-dimensional GIS; and more. Includes case studies in GIS/EM. This book is intended for readers interested in advanced Geographic Information Systems, Spatial Data Processing, or Environmental Modeling.